Code-switching as a means of struggling against the English hegemony at Midlands State University - Tevedzera, Gijimah (Journal for Studies in Humanities and Social Sciences, 2019)
English, as a foreign language has enjoyed superiority over indigenous African languages since the advent of British colonisation in Africa. At Midlands State University English is the language of hegemony. Policy regarding language use stipulates that English is the working language and language of instruction, and indigenous languages are completely disregarded. The study recognises that whilst there are hard and fast rules that speak against the use of indigenous languages, people do not conform to the standard mainly because English is not the language of the people. There are means that are used to operate above the hegemony and code-switching is one such avenue. That being the case, this inquiry examines the extent to which code-switching is used and can serve as a means of struggling against the hegemony of English language at Midlands State University. The study also unpacks the forces that are behind the nurturing of the hegemony of English language. In an attempt to come up with informed decisions, a hybrid theoretical framework comprising the competence and markedness model is adopted. The study is qualitative in nature and data was collected through observation and personal interviews. The study establishes that code-switching is the order of the day in lectures at Midlands State University. It acknowledges the role that is played by code-switching in ensuring that indigenous languages are not completely excluded from domains that are reserved for English language. The study concludes that code-switching is an effective way of struggling against English hegemony since it enhances the use of indigenous languages, particularly Shona in the classroom.